G314(P) Reducing neonatal mortality in a resource poor setting; Experiences from rural Ethiopia. (7th April 2014) - Ledger, E; Candler, T; Mossie, L; Ellis, M
Abstract : Aims: To reduce neonatal mortality rates in two district hospitals in Southern Ethiopia with a package of staff training and infrastructure improvement. A training course in essential neonatal care and resuscitation was provided alongside equipping and refurbishing a new neonatal unit with locally built and sustainable equipment in two seperate locations. Methods: For 11 months during 2012, two paediatric trainees from the UK completed the Voluntary Services Overseas Fellowship in Ethiopia. They were based at two rural hospitals in Southern Ethiopia; Yirgalem General Hospital serving a population of over 3 million with an initial neonatal mortality rate of 22.5%, and Nigist Eleni Mohammed Memorial Hospital (NEMMH) serving a population of over 1.5 million people with an initial neonatal mortality rate of 20.4%. At both hospitals there was no specific provision for neonates prior to intervention. The intervention consisted of a training course in essential neonatal care including neonatal resuscitation for all staff involved in neonatal care following the training of trainers method. This was partnered with the establishment of a separate room for neonates providing respiratory support, phototherapy, feeding support, infection control and treatment of sepsis and adequate thermal control including Kangaroo Mother Care using materials designed and built locally and a layout that maximised the space available but took into account low staffing and monitoring levels. The plan at Yirgalem was implemented over a 6 month period from July 2012 until January 2013 and cost 10, 500 US. After implementing the project at Yirgalem the same model was applied to NEMMH with training, refurbishment and equipment provision completed over a month period at a cost of 6, 715 US. Results: The interventions led to a subsequent reduction in neonatal mortality rates over the next 3 months with a reduction to 7.54% at Yirgalem and 6.7% at NEMMH. Conclusion: The aim of this paper is to provide insight into developing a low cost, high impact, sustainable solution to the challenges of neonatal care in a resource poor setting.